Why do people fail to turn good intentions into action? The role of executive control processes in the translation of healthy eating intentions into action in young Scottish adults - Allan Julia L; Johnston Marie; Campbell Neil (BMC, 2008)
Abstract Background Despite the significant health benefits associated with eating healthily, diet is extremely difficult to change, with the majority of people who intend to eat more healthily failing to do so. Recent evidence has suggested that the ability to turn intentions into actions may be related to individual differences in one facet of executive control - cognitive inhibition (i.e. the ability to inhibit irrelevant information and suppress prepotent responses). The present study investigates the role of this and other executive processes (inhibition, task switching, planning and cognitive flexibility) in the translation of dietary intentions into action. In addition, as the literature suggests that weak executive control may be associated with hyper-responsivity to cues to action, the role of executive processes in susceptibility to environmental food cues and responses to If-Then plans designed to cue intended behaviour are investigated. Methods Future intentions about consumption of fruits and vegetables and snack foods will be measured in a sample of young adults. Actual consumption of the target foods will be recorded with computerised diaries over a subsequent 3-day period. Performance on a battery of established executive control tasks (Go-NoGo, Tower task, Verbal Fluency task and Trail-Making) will be used to predict the discrepancy between intended and actual dietary behaviour. In addition, executive control scores will be used to predict reported susceptibility to environmental food cues and benefit derived from the use of 'If-Then plans' designed to cue intended behaviour. Discussion Our findings will add to understanding about the role of executive control in translating intentions into actions and may demonstrate potential for future public health interventions. If participants with weak executive control are found to be less likely to eat as they intend than those with strong executive control, then interventions that reduce the load on these executive processes may increase chances of successful intention-behaviour translation. If those with weak executive control are found to be more responsive to cues to action they may also benefit more from the use of If-Then plans designed to cue intended behaviour.